2007
DOI: 10.3174/ajnr.a0730
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Pterygoid Muscle Rhabdomyolysis

Abstract: SUMMARY:We report a case of rhabdomyolysis due to acetaminophen overdose involving the lateral pterygoid muscles bilaterally, in addition to the other muscles of the abdomen and pelvis. To the best of our knowledge, involvement of the head and neck muscles by rhabdomyolysis has not been reported previously. The isolated involvement of the lateral pterygoid muscles may be due to the presence of the surrounding pterygoid venous plexus. It is important to be aware of the imaging characteristics of rhabdomyolysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…3 More recently, Jain et al reported low density of the lateral pterygoid muscles on CT with subsequent hyperintensity and contrast enhancement on MRI done several days later in a 28-year-old with psychiatric problems who was admitted to the hospital for an acetaminophen overdose. 4 CT and MRI findings of rhabdomyolysis in the extremities have also been reported, 9,10 and two types of rhabdomyolysis have been described. 9 Type I rhabdomyolysis presents with oedema and the affected muscles reveal homogeneous isointensity to hypointensity on T 1 -weighted images, homogeneous hyperintensity on T 2 -weighted and STIR images and homogeneous enhancement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 More recently, Jain et al reported low density of the lateral pterygoid muscles on CT with subsequent hyperintensity and contrast enhancement on MRI done several days later in a 28-year-old with psychiatric problems who was admitted to the hospital for an acetaminophen overdose. 4 CT and MRI findings of rhabdomyolysis in the extremities have also been reported, 9,10 and two types of rhabdomyolysis have been described. 9 Type I rhabdomyolysis presents with oedema and the affected muscles reveal homogeneous isointensity to hypointensity on T 1 -weighted images, homogeneous hyperintensity on T 2 -weighted and STIR images and homogeneous enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…8 To our knowledge, three cases of rhabdomyolysis in the head and neck have been reported. [2][3][4] Riggs et al reported swelling and a low density area in the left neck muscles on CT and hyperintensity of the muscles and adjacent soft tissues on MRI in a 22-year-old man with heroin and chronic ethanol use. 2 Shah et al reported sonographic findings of rhabdomyolysis of the masseter muscle in a 33-year-old man with ingestion of an unknown quantity of alcohol and drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the craniofacial region, isolated rhabdomyolysis of the lateral pterygoid (8), masseter (9), and sternomastoid (10) muscles associated with acute cocaine intoxication have been described, with initial muscle hypoattenuation on unenhanced CT images, normal or decreased signal intensity on T1-weighted images, and increased signal intensity on T2-weighted images (8)(9)(10). Secondary hyperintensity on T1-weighted images has been reported and attributed to delayed calcium deposition in the affected muscles (8). Here, the right and left longus colli and longus capitis muscles had normal signal intensity on T1-weighted images, while the other neck muscles showed decreased signal intensity.…”
Section: Historymentioning
confidence: 99%
“…CT scans initially show areas of low attenuation within affected muscles, which may become hyperattenuated in later stages, with or without subsequent atrophy. MR imaging shows hyperintensity on T2-weighted images with avid contrast enhancement and may demonstrate T1 hyperintensity later in the course of the disease in some patients [38].…”
Section: Rabdomyolysis Of Musclesmentioning
confidence: 99%